Studi Daya Cerna Protein, Aktivitas Antioksidan dan Sifat Fungsional Tepung Kecambah Kacang Merah (Phaseolus vulgaris L.) Dalam Rangka Pengembangan Pangan Fungsional - Ni Wayan Wisaniyasa; Agus Selamet Duniaji; A.A.G.N. Anom Jambe (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2017)
The objectives of this study were to determine the effect of germination time on protein digestibility, antioxidant activity and functional characteristics of kidney bean (Phaseolus vulgaris L.) sprouts flour and characteristic of kidney bean sprout biscuits. This study used Completely Randomized Design with three replications. This research was conducted with three stages were: a) Making kidney beans sprouts with germination time were 0, 24, 36, 48 and 60 hours. b). Making kidney bean sprouts flour and analysed of protein digestibility by in vitro analysis, antioxidant activity and functional properties of kidney bean sprouts flour. c). Making biscuit from kidney bean sprouts flour and analysed the characteristic of biscuit. The results showed that germination process increased protein digestibility, decreased IC 50% value, increased fat absorption capacity and water but decreased swelling volume and solubility. Protein digestibility ranges from 52.73% to 54.29%, antioxidant activity ranges from 26.33 to 24.77 (IC 50%). Oil absorption capacity ranges from 81.30 to 90.26%, water absorption capacity of flour ranges from 119.56 to 128.03%, swelling power ranges from 3.58 to 3.33 (g/g) and the solubility ranges from 25,86 to 30.11 (%). Based on statistical analysis, the best treatment was kidney bean sprouts with 48 hours of germination. This flour was selected for making biscuits. The best biscuits were obtained from the treatment of 40% wheat and 60% kidney bean sprouts flour with criteria were 2.86% of moisture content, 2.61% of ash content, 19.79% of fat, 8.03% of protein and 66.71% of carbohydrate.